2021
DOI: 10.1007/s10608-020-10193-2
|View full text |Cite
|
Sign up to set email alerts
|

To Approach or to Avoid: The Role of Ambivalent Motivation in Attentional Biases to Threat and Spider Fear

Abstract: Background People with anxiety difficulties show different patterns in their deployment of attention to threat compared to people without anxiety difficulties. These attentional biases are assumed to play a critical role in the development and persistence of anxiety. However, little is known about factors that influence attentional biases to threat. An emerging body of evidence suggests that visual attention to threat varies across the time course according to one's motivation to approach vs. avoid threat. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The purpose of this study was to examine participants' need to attend to threat and to avoid attending to threat during a checking task, to explore whether the need to attend versus avoid mapped onto actual viewing patterns, and to determine whether need to attend and visual attention to threat influenced post-check certainty. Consistent with Nelson et al (2015) and Xu et al (2021) the correlation between motivation to attend to and avoid attending to threat stimuli was quite low (in our case non-significant) in both groups suggesting ambivalence about whether to attend or to avoid. As hypothesized, we found that those with checking concerns (HCC)…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The purpose of this study was to examine participants' need to attend to threat and to avoid attending to threat during a checking task, to explore whether the need to attend versus avoid mapped onto actual viewing patterns, and to determine whether need to attend and visual attention to threat influenced post-check certainty. Consistent with Nelson et al (2015) and Xu et al (2021) the correlation between motivation to attend to and avoid attending to threat stimuli was quite low (in our case non-significant) in both groups suggesting ambivalence about whether to attend or to avoid. As hypothesized, we found that those with checking concerns (HCC)…”
Section: Discussionsupporting
confidence: 85%
“…However, our fourth hypothesis -that greater need to avoid threat would predict greater post-check certainty -was not supported. This hypothesis was based on Nelson et al (2015) and Xu et al (2021) who found that people have the capacity to avoid looking at threat when motivated to do so. Bucarelli and Purdon (2016) found that people with OCD looked less at threat objects than did anxious controls, but their control group comprised people with a ATTENTION TO THREAT DURING CHECKING 20 diagnosis of GAD who may have been more threat sensitive than the control group in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation